Human chromosome telomeres - Barbé-Tuana, Florencia; Grun, Lucas Kich; Pierdoná, Vinícius; de Oliveira, Beatriz Cristina Dias [UNESP]; Paiva, Stephany Cacete [UNESP]; Shiburah, Mark Ewusi [UNESP]; da Silva, Vítor Luiz [UNESP]; Morea, Edna Gicela Ortiz [UNESP]; Fontes, Verônica Silva [UNESP]; Cano, Maria Isabel Nogueira [UNESP] (Springer Nature, 2021)
Telomeres are specialized sequences at the end of linear chromosomes. Its conserved structure and function among eukaryotic cells suggest important evolutionary functions. Telomere dynamics play major roles in chromosomal integrity, stability, cellular replication and aging, performing crucial genome protective functions. In the majority of somatic cells, telomeres shorten in each round of cell replication. Whereas short telomeres are a trigger for apoptosis, accelerated attrition is a hallmark of aging, present in senescent and tumoral cells. Compensation for erosion in germinal and progenitor cells is accomplished by the telomerase enzyme, composed of a catalytic (TERT) and a RNA template (TR) subunits. Telomerase activity is tightly controlled with reactivation central for tumoral transformation. Clinical evidence suggests that telomeres' shortening that causally contributes to the establishment of specific progeria syndromes phenotypes are telomeropathies. In other cases, aging is accompanied by an abrupt telomere shortening in the context of chronic diseases, proposing telomeres length as an important biological pace marker for progression of various pathologies and aging. Because cancer cells reactivate TERT to compensate for telomeric loss, in the last decades, telomerase and the telomeres biology field have been subject to intense research in search for therapeutical targets for cancer. This chapter mainly focuses on basic telomere description and synthesis accomplished by the reverse transcriptase telomerase and its regulation. A final section addresses the understanding of telomeres in health and its contribution to cancer with therapeutic potentials for targeted inhibition.
Keywords: Aging; Cancer, senescence, Shelterin complex; Telomerase; Telomeres; Telomeropathies, TERT, TERRA